2018
DOI: 10.1042/bsr20180420
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA SNHG3 enhances the malignant progress of glioma through silencing KLF2 and p21

Abstract: As a newly discovered long non-coding RNA, small nucleolar RNA host gene 3 (SHNG3) has been reported to be dysregulated in certain cancers. Nevertheless, the details about clinical values and biological effects of SNHG3 on glioma are still covered. In this paper, we determined the expression level of SNHG3 in glioma tissues and cells and evaluated the effect of SNHG3 expression on the prognosis of glioma patients. The functional assays were applied to define the effects of SNHG3 on the biological behaviors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
73
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(74 citation statements)
references
References 29 publications
(29 reference statements)
1
73
0
Order By: Relevance
“…For instance, up‐regulated lncRNA SNHG3 is connected to the serious progression and poor prognosis of hepatocellular carcinoma 13 . SNHG3 can promote the progression of glioma by reducing the expression of KLF2 and p21 15 . Also, lncRNA SNHG3 can modulate GSK3β/β‐catenin pathway to regulate the progression of ovarian cancer 16 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, up‐regulated lncRNA SNHG3 is connected to the serious progression and poor prognosis of hepatocellular carcinoma 13 . SNHG3 can promote the progression of glioma by reducing the expression of KLF2 and p21 15 . Also, lncRNA SNHG3 can modulate GSK3β/β‐catenin pathway to regulate the progression of ovarian cancer 16 .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, lncRNA625 is up‐regulated in prostate cancer cells and sponges miR‐432 to activate the Wnt/β‐catenin signaling for modulating the progression of prostate cancer 12 . Also, lncRNA small nucleolar RNA host gene 3 (SNHG3) has been identified as oncogene in many cancers, such as hepatocellular carcinoma, colorectal cancer, glioma, ovarian cancer, and osteosarcoma 13‐17 . However, the role of SNHG3 is still not clear in prostate cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) act as critical modulators in many diseases by participating in cell cycle, growth, differentiation, inammation, metastasis, apoptosis and drug resistance. [6][7][8] Exosomes are vesicles secreted by cells and they could transfer and exchange lncRNAs between tumors and extracellular microenvironment. 9 LncRNA PTEN pseudogene-1 (PTENP1) mapped on chromosome 10 was recognized as a tumor suppressor to reduce tumorigenesis and progression of various cancers.…”
Section: Introductionmentioning
confidence: 99%
“…SNHG3 has been identified as a novel lncRNA; therefore, there were limited investigations studying the functions of SNHG3 in various tumors [10,11,13]. It was reported that SNHG3 was overexpressed in liver cancer, breast cancer, and colorectal cancer, which was associated with poor survival and prognosis in tumor-bearing patients [10,11,13,18,27]. Importantly, SNHG3 was identified as a potential oncogene in breast cancer based on previous studies which focused on cancer cell-autonomous function of SNHG3 [28].…”
Section: Discussionmentioning
confidence: 99%
“…Small nucleolar RNA host gene 3 (SNHG3) was discovered as a new lncRNA, which located on 1q35.3 [10]. Accumulating evidence demonstrates that the expression of SNHG3 was increased in variety types of tumor tissues such as breast cancer, hepatocellular carcinoma, and colorectal cancer, resulting in increased proliferation and metastasis of tumor cells and poor survival of tumor-bearing patients [10][11][12][13]. LncRNA was able to be released to the extracellular spaces by exosomes or in protein complexes or lipid carriers [14].…”
Section: Introductionmentioning
confidence: 99%